2011
DOI: 10.1242/jeb.053348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shell morphology on mechanics of zebra and quagga mussel locomotion

Abstract: SUMMARYAlthough zebra mussels (Dreissena polymorpha) initially colonized shallow habitats within the North American Great Lakes, quagga mussels (Dreissena bugensis) are becoming dominant in both shallow-and deep-water habitats. Shell morphology differs among zebra, shallow quagga and deep quagga mussels but functional consequences of such differences are unknown. We examined effects of shell morphology on locomotion for the three morphotypes on hard (typical of shallow habitats) and soft (characteristic of dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…They plow through subsurface sediment layers [47], thereby dislodging particulate matter and nutrients from the sediment into the overlying water [32], potentially increasing TSS and stimulating pelagic algal production, both of which may result in increased water turbidity. Peyer et al [48] observed zebra mussel moving 20 cm within 20 h, while quagga mussel moved 29 cm in the same time. Quagga mussels are also more often found on soft sediment than zebra mussels [44].…”
Section: Discussionmentioning
confidence: 99%
“…They plow through subsurface sediment layers [47], thereby dislodging particulate matter and nutrients from the sediment into the overlying water [32], potentially increasing TSS and stimulating pelagic algal production, both of which may result in increased water turbidity. Peyer et al [48] observed zebra mussel moving 20 cm within 20 h, while quagga mussel moved 29 cm in the same time. Quagga mussels are also more often found on soft sediment than zebra mussels [44].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that factors such as hydrophobicity and substrate stiffness may elicit a different response for zebra and quagga mussels, respectively. Although our approach is limited by the fact that fully developed mussels were placed on the substrate rather than veliger mussels, and that the quagga mussel population utilized may not represent all possible morphotypes 24 , 25 , 30 , this nonetheless suggests that zebra mussels display a more universal adhesion than quagga mussels. Previously, it has been reported that zebra mussels adhered more on hard substrates and quagga mussels on soft substrates as observed in natura , but our results suggest this may only be the case in soft and hard substrates that naturally exist in nature, such as silts, clays, and stones 31 .…”
Section: Resultsmentioning
confidence: 99%
“…In bivalves, the shell elongation , the shell dissymmetry , and the ventral convexity (defined in Figure 1) would likely be the main traits of the shell outline captured at first glance. Also, these parameters may arguably quantify some traits of shell contour potentially having significant functionalities, relevant to the animal survival success ( and/or : [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]; : [29]). Parallel to these three functionally relevant parameters , , and , three growth-based parameters , , and provide an alternative description of the shell outline, deliberately focused, this time, upon the developmental process which, finally, generate this particular shell outline.…”
Section: Linking the Main Traits Of Shell Outline To The Growth-basedmentioning
confidence: 99%